Insecurity and University Education in Nigeria - Abiodun, Olowonefa Jethro (MultiTech Publisher, 2024)
This paper assessed the impact of insecurity on university education in Nigeria. The paper employed secondary data that were collected from both print and online publications. The paper established that insecurities have affected investment in universities and led to an unstable academic calendar and the deaths of academic staff, students, and researchers. The paper also discovered that insecurities have affected programs of universities, which include teaching, research, and community service programs. Based on these findings, the paper recommends that the government should immediately address all issues breeding insecurities in Nigeria. The government should increase investment in the security sector. The government should employ more security personnel and deploy artificial intelligence to universities for effective management of securities in the universities across Nigeria.